Wastewater treatment using activated sludge on a laboratory scale - Méndez, L. (2004)
The experiment was carried out at the laboratory scale. For this purpose a system with 6 mini reactors was designed, adapted from the literature. The used equations were deduced from the Eckenfelder (1970) and Metcalf & Eddy (1998) proceedings. The kinetics constants of biological growth at laboratory level were obtained using the activated sludge method. The obtained kinetic constants with synthetic wastewater were: a: 0,8763 (Parameter of oxygen utilization to substrate oxidation). b: 0,0744 (Parameter of oxygen utilization to substrate oxidation in the endogenous respiration). Y: 0,0494 (Ratio of the mass of cells formed to the mass of substrate consumed). kd: 0,00048 d-1 (Endogenous decay coefficient). k: 0,0025 h-1.L/mg (Velocity constant of substrate utilization). The wastewater were supplied to each mini reactor trough a dosificator and a peristaltic pump. It was found difficulty in the water flow distribution. It is recommended to carry out the experiment, pumping wastewater with a peristaltic pump to each mini reactor, because the used dosificator got obstructed frequently.